2018
DOI: 10.1039/c8ra04417a
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation, point defects and hydrogen storage properties of monolayer TiS3: an ab initio study

Abstract: The possibility of H 2 molecule adsorption on the basal plane of monolayer TiS 3 at various sites has been studied. Among the studied adsorption sites, few sites were found to be suitable for physisorption with binding energy up to 0.10 eV per H 2 . To increase the activity of hydrogen sorption, the possibility of generating S-vacancies, by removing sulfur atoms from the basal plane of monolayer TiS 3, was investigated. Despite the fact that the structures containing vacancies were found to be stable enough, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…In the subsequent heating cycles (2-6) we observe a gradual increase in the value of the exponent 𝛼 toward 0, signifying an increase in the density of traps and/or an effect on the lower effective light injection levels due to the lower absorption in the visible range of the spectrum by the TiO2 (see Section S1 of the Supporting Information). The exponent 𝛼 saturates around −0.25, a value larger than the starting value of −0.4, which indicates that the final TiO2 material contains a larger trap density than the starting TiS3 material that favors monomolecular recombination between photoexcited carriers [45,46].…”
Section: Electronic and Optoelectronic Characterizationmentioning
confidence: 89%
“…In the subsequent heating cycles (2-6) we observe a gradual increase in the value of the exponent 𝛼 toward 0, signifying an increase in the density of traps and/or an effect on the lower effective light injection levels due to the lower absorption in the visible range of the spectrum by the TiO2 (see Section S1 of the Supporting Information). The exponent 𝛼 saturates around −0.25, a value larger than the starting value of −0.4, which indicates that the final TiO2 material contains a larger trap density than the starting TiS3 material that favors monomolecular recombination between photoexcited carriers [45,46].…”
Section: Electronic and Optoelectronic Characterizationmentioning
confidence: 89%
“…To reduce the synthesis time of TiS 3 , titanium (Ti) foil and high purity S powder are usually directly reacted in a sealed ampoule. The reaction time required for this method is usually more than 3 days. ,,, In addition, no matter which method above is used to synthesize TiS 3 crystal, it needs to be peeled off and transferred to the target substrate for further theoretical research and micro-nano device manufacturing, , which seriously limits the device application of TiS 3 .…”
Section: Introductionmentioning
confidence: 99%
“…26,27 It was shown that these 2D materials display diverse electronic, optical, and magnetic properties for a wide range of technological applications, such as optoelectronics, spintronics, catalysts, chemical and biological sensors, supercapacitors, solar cells, nanotribology, [28][29][30] hydrogen production, and lithium or sodium ion batteries. 31,32 Very recently, the synthesis of ultrathin, 2D black phosphorus, through exfoliation from its layered bulk counterparts, has brought the suspended 2D monolayers and multilayers of group-VA elements [33][34][35] into the focus of current research. Specifically, the field effect transistors (FETs) fabricated on few-layer black phosphorus 33 showed a high field-effect mobility up to 1000 cm 2 /V s at room temperature for a thickness of $10 nm.…”
Section: Introductionmentioning
confidence: 99%